Respuesta :
[tex]\log_a(x) +\log_a(y) =\log_a(x\times y) \\ \\ \log_3(81)+\log_3(81)=\log_3(81\times81) =\log_3(6561) [/tex]
A. log3 6561
[tex]\log_3(6561)=log_3(3^8)=8 \\ [/tex]
В. log3 (3^8)
С. 8
A. log3 6561
[tex]\log_3(6561)=log_3(3^8)=8 \\ [/tex]
В. log3 (3^8)
С. 8
Answer:
Option A , B and C are correct
Step-by-step explanation:
Using the logarithmic rules:
[tex]\log_b m + \log_b n = \log_b (mn)[/tex]
[tex]\log_b b^m = m[/tex]
Given the expression:
[tex]\log_3 81+ \log_3 81[/tex]
Apply the logarithmic rules:
[tex]\log_3 (81 \cdot 81)[/tex] ....[1]
⇒[tex]\log_3 6561[/tex]
[1] ⇒
[tex]\log_3 (81 \cdot 81)[/tex]
We can write this as:
[tex]\log_3 (3^4 \cdot 3^4) = \log_3 (3^8)[/tex]
apply the logarithmic rules we get;
[tex]\log_3 3^8 = 8[/tex]
Therefore, the expression are equivalent to the [tex]\log_3 81+ \log_3 81[/tex] are:
[tex]\log_3 6561[/tex]
[tex]\log_3 (3^8)[/tex] and
8